Rezension von: Planck, Dieter; Beck, Willi; Der Limes in Südwestdeutschland - Pastor, Egil (Württembergisch Franken, 1988)
Dieter Planck; Willi Beck: Der Limes in Südwestdeutschland. Limeswanderweg Main - Rems - Wörnitz. 2., neu bearb. Aufl. Stuttgart: Theiss 1987. 156 S., 134 Abb. u. 1 Wanderkarte.